Empagliflozin (BI 10773), a Potent and Selective SGLT2 Inhibitor, Induces Dose‐Dependent Glucosuria in Healthy Subjects. Issue 2 (27th March 2013) - Seman, Leo; Macha, Sreeraj; Nehmiz, Gerhard; Simons, Gudrun; Ren, Bailuo; Pinnetti, Sabine; Woerle, Hans J.; Dugi, Klaus
Abstract Empagliflozin is an orally available, selective inhibitor of sodium glucose cotransporter 2. In this study, single oral doses of empagliflozin from 0.5 to 800 mg were not associated with any clinically significant safety concerns in healthy male volunteers. The incidence of adverse events (AEs) was similar in subjects receiving placebo (22.2%) or empagliflozin (25.0%) in the single rising dose part of the study and after 50 mg empagliflozin under fed (28.6%) or fasted (28.6%) conditions. The most frequent AE was headache. No clinically relevant changes in laboratory or electrocardiogram (ECG) measurements were observed. Single oral doses of empagliflozin were rapidly absorbed, reaching peak levels after 1.0–2.1 hours. Increases in empagliflozin exposure were roughly dose‐proportional and a dose‐dependent increase in urinary glucose excretion was observed for empagliflozin doses up to 100 mg. After ingestion of 50 mg empagliflozin in conjunction with a high‐fat, high‐calorie meal, no clinically relevant changes in exposure were found, indicating that empagliflozin can be administered independent of food. Empagliflozin up to 800 mg did not generate clinically significant safety concerns in healthy male subjects. The pharmacokinetic properties of empagliflozin support once daily administration independent of food.